Nutritional and Physiological Functions of Amino Acids in Pigs - Blachier, Francois.; Wu, Guoyao.; Yin, Yulong. (Springer Vienna : Imprint: Springer, 2013)
This book provides developmental data regarding piglets (with a focus on the gastrointestinal tract), data related to amino acid metabolism in pigs, data related to nutritional and physiological functions of amino acids in pigs, nutritional requirements for amino acids in pigs, signaling roles of amino acids, methodological aspects in amino acid research and the pig model for studying amino acid-related human diseases.